Hepatitis B and C Virus Infections among Blood Donors in Blood Transfusion Center, Pokhara, Nepal: Seroprevalence and its Associated Risk Factors - Shah, Gyanendra Bikram; Gurung, Krishna; Baral, Bharat Prasad; Gurung, Ram Raja; Bhattachan, Balkrishna (Nepal Journal of Biotechnology, 2019)
Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) infections lead to chronic diseases and are the most common causes of liver cirrhosis and cancer in developing countries like Nepal. The study is carried out to determine the seroprevalence of HBV and HCV by using a Rapid kit method and Elisa Method to find out its risk factors. The cross-sectional study was done among blood donating people from 16th August 2016 to 19th November 2016. Blood donors in Pokhara Valley were screened for anti-HCV antibodies, anti-HBV antibodies using third generation ELISA kits and automated ELISA Processor in serology laboratory at Central Blood Transfusion Service (CBTS) of Nepal Red Cross Society (NRCS) in Pokhara, Nepal. 1777 (87.2%) units were male blood donors and 260 (12.6%) units were female donors out of 2037 participants. Gender wise, the ratio between male and female was 1:0.1. HBV and HCV infection rate in blood donors were detected at 0.7% (15/2037) and 0.5% (8/2037) respectively. HBV infection rate in volunteer blood donor people was 0.7% (14/1881) which was higher than the replacement donors i.e. 0.6% (1/156). Similarly, in HCV infection rate in volunteer donor were 0.4% (8/1881). HBV infected people are detected higher than the HCV infected people among the blood donors. In addition, there was no significant relationship between positive results of HBV and HCV tests with the gender, age, tattoo, donor type.